2018
DOI: 10.1111/cas.13467
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of 15‐hydroxyprostaglandin dehydrogenase by interleukin‐1β from activated macrophages leads to poor prognosis in pancreatic cancer

Abstract: Chronic inflammation has a crucial role in cancer development and the progression of various tumors, including pancreatic ductal adenocarcinoma (PDAC). The arachidonate cascade is a major inflammatory pathway that produces several metabolites, such as prostaglandin E2. The enzyme 15‐hydroxyprostaglandin dehydrogenase (15‐PGDH) degrades prostaglandin and is frequently decreased in several types of cancer; however, the molecular mechanisms of 15‐PGDH suppression are unclear. The current study was carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…IL-1β derived from TAMs suppresses the expression of 15-hydroxyprostaglandin dehydrogenase (15-PGDH), an enzyme involved in prostaglandin degradation in PDAC cells, which results in tumor growth and poor prognosis for PDAC patients [ 145 ]. It can also increase COX-2 expression in human breast cancer cells, thus contributing to cancer progression [ 146 ].…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…IL-1β derived from TAMs suppresses the expression of 15-hydroxyprostaglandin dehydrogenase (15-PGDH), an enzyme involved in prostaglandin degradation in PDAC cells, which results in tumor growth and poor prognosis for PDAC patients [ 145 ]. It can also increase COX-2 expression in human breast cancer cells, thus contributing to cancer progression [ 146 ].…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…A number of studies have shown that inflammation triggered infiltration of immune cells in the PAAD microenvironment was closely associated with pancreatic cancer cells growth, metastasis and poor clinical outcomes. [ 24 , 28 , 29 ] In this study, we found that a greater immune score was significantly correlated with advanced TNM stage (stage IIA, stage IIB, stage III, and stage IV) ( P = .0367), which indicate that interactions of the surrounding microenvironment play an important role in the development and progression of PAAD.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, IL-1β facilitates cell migration by stimulating the synthesis of HIF-1α under non-hypoxic conditions (Filippi et al, 2015). It also causes angiogenesis by increasing CxCL8 / CXCR1 (Filippi et al, 2015), VEGF (Voronov et al, 2003), EGFR and IL-8 (Lee et al, 2015), as well as secondary tumorigenesis with a greater production of ROS, COX2, NADPH oxidase and reduction of 15-PGDH (Arima et al, 2017). Some authors attribute the rise in IL-1β plasma to an increased risk of cervical cancer in women with polymorphisms (Qian et al, 2010).…”
Section: Discussionmentioning
confidence: 99%